Clonal propagation of Dracaena fragrans cv. Victoria through tissue culture technology (Jahangirnagar University Journal of Biological Sciences, 2020)
Micropropagation of Dracaena fragrans cv.Victoria was conducted using the young, tender and disease-free leaves and nodal segments as explants collected from the local market of Savar, Dhaka. Surface sterilization of the explants pretreated with a liquid detergent and then 0.2% HgCl2 for 4-5 minutes produces maximum contamination free explants without any toxicity. After surface sterilization, different explants were inoculated on gelrite gelled MS medium supplemented with different concentrations of 2,4-D for callus induction and with different concentrations and combinations of BAP and NAA for direct shoot induction. Nodal explants showed high callus induction potentiality (80%) on MS medium supplemented with 1.5 mg/l 2,4-D. The highest frequency of direct shoot induction from nodal segment was 80% and the number of shoots per nodal segment was(5.28±1.17) when they were cultured on MS medium supplemented with 3.0 mg/l BAP and 0.3 mg/l NAA. The highest shoot multiplication (83.33%) with maximum number of shoot per unit callus (5.62±1.24) and maximum shoot length (3.27±0.82 cm) was observed when the nodal calli were transferred in gelrite gelled MS medium in combination with 4.5 mg/l BAP and 0.5 mg/l NAA. Additionally, the incorporation of 4% sucrose and 10% coconut water with the above mentioned medium showed the satisfactory shoot growth and development with an average 7.84±1.30 shoots per unit of callus which was 4.21±0.78 cm in length. Moreover, addition of 3.0 mg/l GA3 with the above mention medium showed highest rate of shoot elongation (5.83±2.31cm). For root induction, in vitro raised shoots were transferred onto half-strength of MS liquid medium augmented with different concentrations and combinations of auxins (IBA and NAA). Maximum rooting (75%) were observed in halfstrength MS liquid medium supplemented with 0.5 mg/l IBA. After appropriate rooting the plantlets were successfully acclimatized (85% survival) when they were cultured in polybag containing (1:1:1) garden soil, sand and compost mixture before transferred to soil. Regenerated plants were morphologically identical with mother plants and showed their uniform growth in field condition.Jahangirnagar University J. Biol. Sci. 8(2): 1-11, 2019 (December)